Investigating the dynamics of MCMV-specific CD8+ T cell responses in individual hosts - Gabel, Michael; Baumann, Nicolas S.; Oxenius, Annette; Graw, Frederik (Frontiers in immunology, 2019)
Infection by Cytomegalovirus (CMV) is characterized by the massive expansion and continued maintenance of CMV-specific CD8+ T cells for certain CMV-derived peptides. This phenomenon called "memory inflation" has made CMV a primary target for the generation of T cell based vaccine vectors against various diseases. However, many aspects concerning the generation and maintenance of the inflationary CD8+ T cell response still remain to be resolved. In this study, we combined experimental data and mathematical models to analyze the dynamics of circulatory inflationary CD8+ T cells within individual mice infected by MCMV. Obtaining frequent measurements on the number and frequency of CMV-specific CD8+ T cells up to 70 days post infection, we find that mathematical models assuming differing viral stimuli during acute infection and the inflationary phase provide a better description for the observed dynamics than models relying on similar viral stimuli during both phases. In addition, our analysis allowed a detailed quantification of the different phases of memory inflation within individual mice (1st-expansion - contraction - 2nd expansion/maintenance) indicating remarkable consistency of the timing of these phases across mice, but considerable variation in the size of the individual responses between mice. Our analysis provides a first step towards generating a mechanistic framework for analyzing the generation and maintenance of inflationary CD8+ T cells while accounting for individual heterogeneity. Extending these analyses by incorporating measurements from additional compartments and more prolonged sampling will help to obtain a systematic and quantitative understanding of the factors regulating the process of memory inflation.
Das Pluszeichen ist im Titel hochgestellt
Gesehen am 11.11.2019